Composite solid electrolyte and preparation method thereof
By using a combination of PEO matrix, lithium salt, composite modifier and ethoxy (pentafluoro)cyclotriphosphazene in solid electrolytes, the challenges of solid electrolytes in ion conductivity, interface stability and processing technology are solved, and the long life and high efficiency of high-performance batteries are achieved.
Patent Information
- Application Number
- CN202510005336.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The existing solid electrolytes have challenges in ionic conductivity, interface stability and processing technology, resulting in limited application of their high-performance batteries.
The composite solid electrolyte is adopted to optimize the material combination and preparation process through the combination of PEO matrix, lithium salt, composite modifier and ethoxy (pentafluoro)cyclotriphosphazene to improve the comprehensive performance of the electrolyte.
Maintaining stable conductivity and structural integrity in multiple charge and discharge cycles is achieved, significantly extending the service life of the battery, and improving the overall efficiency and reliability of the battery.
Smart Images

Figure BDA0005226692360000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite solid electrolyte and a preparation method thereof. Background Art
[0002] As the global demand for efficient, reliable and safe energy storage devices continues to grow, lithium-ion batteries, as one of the most widely used battery technologies, have played an important role in portable electronic devices, electric vehicles and energy storage systems. However, traditional lithium-ion batteries mainly use liquid electrolytes, which have safety hazards such as flammability, leakage and limited life, which to some extent restrict their application in a wider range of fields.
[0003] In order to solve the above problems, solid electrolytes have received widespread attention as a potential material to replace liquid electrolytes. Compared with liquid electrolytes, solid electrolytes have higher safety, wider electrochemical window and better thermal stability, which can significantly improve the overall performance and service life of the battery. In recent years, the research on solid electrolyte materials has made significant progress, mainly including sulfide, oxide and polymer-based solid electrolytes. However, the existing solid electrolytes still face many challenges in terms of ionic conductivity, interface stability and processing technology. For example, the ionic conductivity of some solid electrolyte materials at room temperature is low, which limits their application in high-performance batteries; in addition, the poor interface compatibility between solid electrolytes and electrode materials can easily lead to an increase in the internal impedance of the battery, affecting the battery's charge and discharge efficiency and cycle life.
[0004] As an important component of lithium-ion batteries, solid electrolytes have various material types, which are mainly divided into three categories: sulfide electrolytes, oxide electrolytes and polymer electrolytes. Each type of material has unique performance advantages and application potential.
[0005] Sulfide electrolytes are known for their high ionic conductivity and good processing properties. Typical examples include Li 10 GeP2S 12 (LGPS) and Li7P3S 11 (LPS). These materials exhibit excellent lithium ion conductivity at room temperature, typically reaching 10 -3 S / cm or above, close to the conductivity level of liquid electrolytes. In addition, sulfide electrolytes have low interfacial impedance, which is conducive to good contact between electrodes and electrolytes. However, sulfide materials are deficient in moisture resistance and chemical stability, and are easily reacted with moisture or carbon dioxide in the air, limiting the environmental conditions for their practical application.
[0006] Oxide electrolytes have attracted attention for their excellent chemical stability and wide electrochemical window. Typical representatives include Li7La3Zr2O12 (LLZO) and Li 1.5 Al 0.5 Ge 1.5 (PO4)3(LAGP). These materials show good stability under high temperature and high voltage conditions and are suitable for the needs of high energy density batteries. Although the ionic conductivity of oxide electrolytes is generally lower than that of sulfide electrolytes, their high mechanical strength helps to inhibit dendrite growth inside the battery and improve safety. However, oxide electrolytes are difficult to process, usually requiring high temperature sintering, and have poor interface compatibility with certain electrode materials, which increases the complexity of battery manufacturing.
[0007] Polymer electrolytes have become a research hotspot due to their flexibility and processing convenience, and a typical example is polyethylene oxide (PEO)-based electrolytes. The ionic conductivity of polymer electrolytes at room temperature is relatively low, usually around 10 -4 S / cm, but its conductivity can be significantly improved by introducing plasticizers, nanofillers or cross-linking structures. At the same time, polymer electrolytes have good interface compatibility and mechanical flexibility, which helps to achieve close bonding between electrodes and electrolytes and reduce interface impedance.
[0008] CN118136940A discloses a PEO-based solid electrolyte and a preparation method thereof. The PEO-based solid electrolyte is prepared by solution casting using polyethylene oxide as the matrix of the solid electrolyte, lithium bis(trifluoromethanesulfonylimide) as the lithium salt, and acetonitrile as the solvent. The addition of lithium bis(trifluoromethanesulfonylimide) effectively improves the room temperature ionic conductivity of the polyethylene oxide-based solid electrolyte, and the electrochemical window of the prepared solid electrolyte membrane can be adjusted by changing the proportion of the lithium salt.
[0009] However, the thermal stability and long-term cycle stability of polymer electrolytes still need to be further improved to meet the requirements of high-performance batteries. Based on this, the present invention proposes a composite solid electrolyte and a preparation method thereof, aiming to improve the comprehensive performance of the electrolyte by optimizing the material combination and preparation process, and provide an advanced solution for the development of high-performance solid-state batteries. Summary of the invention
[0010] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide a composite solid electrolyte and a method for preparing the same. In multiple charge and discharge cycles, the composite solid electrolyte of the present invention can effectively resist interfacial side reactions, maintain stable electrical conductivity and structural integrity, and significantly extend the service life of the battery; at the same time, the electrolyte has good interface adaptability, can achieve stable interface contact with various positive and negative electrode materials, reduce interface impedance, and improve the overall efficiency and reliability of the battery.
[0011] In order to achieve the above object, the present invention adopts the following technical solution:
[0012] A composite solid electrolyte is made of the following components by weight: 60-80 parts of PEO matrix, 15-35 parts of lithium salt, 10-20 parts of composite modifier, and 3-8 parts of ethoxy (pentafluoro) cyclotriphosphazene.
[0013] Preferably, the preparation method of the composite modifier comprises the following steps:
[0014] (1) Dispersing mesoporous silica and KH570 in anhydrous ethanol, adding triethanolamine, refluxing reaction, filtering, washing with alcohol, and drying the product to obtain pretreated silica;
[0015] Introduction of organic functional groups: The hydroxyl groups (-Si-OH) on the surface of mesoporous silica react with the alcohol groups in KH570, undergo dehydration condensation under the catalysis of triethanolamine, generate silicon-oxygen bonds (-Si-O-Si-) and fix the KH570 molecules. During this process, the allyl end of KH570 remains unreacted and becomes the active site for subsequent polymerization reactions. The reaction is promoted by reflux conditions to ensure that the coupling agent fully covers the silica surface.
[0016] Preferably, in step (1), the usage ratio of mesoporous silica, KH570, anhydrous ethanol and triethanolamine is 10 g: 0.3-3 g: 50-100 mL: 0.15-1.5 mL.
[0017] Preferably, in step (1), the reflux reaction conditions are 50-80° C. for 2-6 hours.
[0018] (2) dispersing the pretreated silica in ethyl acetate, ultrasonically treating, then adding hexafluorobutyl acrylate and polyethylene glycol methyl ether acrylate, continuously introducing nitrogen, adding azobisisobutyronitrile, stirring to react, cooling, centrifuging, washing, and drying the product to obtain the composite modifier.
[0019] In-situ free radical polymerization to form a polymer layer: The organic functional groups on the surface of pretreated silica are used to initiate the free radical polymerization of hexafluorobutyl acrylate (HFMA) and polyethylene glycol methyl ether acrylate (PEGMEMA) to form a uniform polymer layer. Azobisisobutyronitrile (AIBN) decomposes at a suitable temperature to generate free radicals, which initiate the addition polymerization of monomers from the allyl end of KH570, causing HFMA and PEGMEMA to undergo chain growth reactions on the surface of silica to form a dense and well-connected polymer network.
[0020] Preferably, in step (2), the usage ratio of pretreated silica, ethyl acetate, hexafluorobutyl acrylate, polyethylene glycol methyl ether acrylate, and azobisisobutyronitrile is 10 g: 100-150 mL: 10-15 mL: 15-20 mL: 0.05-0.5 g.
[0021] Preferably, in step (2), the ultrasonic treatment is performed for 10 to 30 minutes; the stirring reaction conditions are 60 to 75° C. and the stirring reaction is performed for 4 to 12 hours; and the product is washed with ethyl acetate for 3 to 5 times.
[0022] Preferably, the lithium salt is one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium chloride.
[0023] The present invention also claims protection for a method for preparing the composite solid electrolyte, comprising the following steps: adding a PEO matrix to a solvent, mixing evenly, then adding a lithium salt, a composite modifier, and ethoxy (pentafluoro) cyclotriphosphazene, stirring and dispersing evenly to obtain a casting slurry, casting the slurry into a film, and after the solvent evaporates, obtaining the composite solid electrolyte.
[0024] Preferably, the solvent is one or more of acetonitrile, acetone, DMF, and NMP; and the mass ratio of the PEO matrix to the solvent is 1:5-10.
[0025] Preferably, the stirring and dispersing conditions are stirring and dispersing at 20 to 80° C. for 1 to 12 hours.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention provides a composite solid electrolyte. First, the PEO matrix, as the main component, provides excellent mechanical strength and flexibility, ensuring the structural stability and crack resistance of the electrolyte membrane. The addition of lithium salt significantly improves the ionic conductivity of the electrolyte, ensuring the efficient migration of lithium ions, thereby improving the overall performance and charge and discharge efficiency of the battery. The composite modifier improves the compatibility between the PEO matrix and mesoporous silica by grafting polyethylene glycol methyl ether acrylate and hexafluorobutyl acrylate, optimizes the ion migration path, and reduces the crystallinity of PEO, thereby effectively improving the ionic conductivity of the electrolyte. At the same time, the introduction of ethoxy (pentafluoro) cyclotriphosphazene significantly improves the thermal stability and flame retardant properties of the electrolyte, and enhances the safety of the electrolyte under high temperature and high voltage environments. In summary, the composite solid electrolyte of the present invention greatly improves the safety and stability of the material while ensuring high ionic conductivity, and is expected to significantly extend the service life of the battery and improve its overall performance.
[0028] 2. The present invention provides a composite modifier, which first uses KH570 to modify mesoporous silica, thereby enhancing the organic compatibility of the surface of mesoporous silica and the interaction with the PEO matrix. Subsequently, hexafluorobutyl acrylate and polyethylene glycol methyl ether acrylate are reacted to generate a polymer in situ on the surface of the modified mesoporous silica. This process not only makes the mesoporous silica more evenly dispersed in the PEO matrix and improves the overall uniformity of the electrolyte, but also reduces the crystallinity of PEO through the grafted polyethylene glycol methyl ether acrylate, thereby promoting the transmission of ions. In addition, the polyfluorinated groups in the composite modifier provide additional channels for the diffusion of lithium ions, and lithium ions achieve efficient migration through the adsorption and desorption process with the polyfluorinated groups. Fluorocarbon groups, as Lewis basic sites, help to adsorb and stabilize lithium ions, optimize their migration paths in the electrolyte, improve the overall ionic conductivity, and synergistically improve lithium ion conductivity with polyethylene glycol methyl ether acrylate. In addition, the rich pore structure of mesoporous silica nanoparticles provides more lithium ion transmission paths, shortens the transmission distance, makes the lithium ion flux more uniform, prolongs the cycle life and effectively prevents the rapid formation of lithium dendrites. The modified mesoporous silica significantly improves the thermal and electrochemical stability of polymer solid electrolytes, broadens its application temperature range, slows down the attenuation rate of electrolyte performance, and enhances the mechanical strength of solid electrolytes, reducing the risk of lithium dendrite puncture. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0030] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.
[0031] PEO molecular weight 60000Da~8000000Da, purchased from Aladdin Chemical;
[0032] The pore size of mesoporous silica is 2-10nm, the diameter is 100-300nm, and the specific surface area is ≥900m 2 / g, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0033] A method for preparing a composite solid electrolyte comprises the following steps:
[0034] (1) Dispersing 10 g of mesoporous silica and 0.3-3 g of KH570 in 50-100 mL of anhydrous ethanol, adding 0.15-1.5 mL of triethanolamine, and reacting at 50-80° C. for 2-6 h, filtering the product, washing with alcohol, and drying it to obtain pretreated silica;
[0035] (2) dispersing 10 g of pretreated silica into 100-150 mL of ethyl acetate, ultrasonically treating for 10-30 min, then adding 10-15 mL of hexafluorobutyl acrylate and 15-20 mL of polyethylene glycol methyl ether acrylate, continuously introducing nitrogen, adding 0.05-0.5 g of azobisisobutyronitrile, stirring and reacting at 60-75° C. for 4-12 h, cooling the product, centrifuging, washing with ethyl acetate for 3-5 times, and drying to obtain the composite modifier;
[0036] (3) Add 60 to 80 parts of PEO matrix to 300 to 800 parts of solvent, mix well, then add 15 to 35 parts of lithium salt, 10 to 20 parts of composite modifier, and 3 to 8 parts of ethoxy (pentafluoro) cyclotriphosphazene, stir and disperse at 20 to 80° C. for 1 to 12 hours to obtain a casting slurry, cast the slurry into a film, and after the solvent evaporates, obtain the composite solid electrolyte.
[0037] The solvent is one or more of acetonitrile, acetone, DMF, and NMP; the lithium salt is one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium chloride.
[0038] The present invention will be further described below through specific embodiments.
[0039] Example 1
[0040] A method for preparing a composite solid electrolyte comprises the following steps:
[0041] (1) Dispersing 10 g of mesoporous silica and 3 g of KH570 in 100 mL of anhydrous ethanol, adding 1.5 mL of triethanolamine, and reacting at 80° C. for 2 h, filtering the product, washing with alcohol, and drying to obtain pretreated silica;
[0042] (2) dispersing 10 g of pretreated silica into 100 mL of ethyl acetate, ultrasonically treating for 30 min, then adding 15 mL of hexafluorobutyl acrylate and 15 mL of polyethylene glycol methyl ether acrylate, continuously introducing nitrogen, adding 0.5 g of azobisisobutyronitrile, stirring and reacting at 75 ° C for 4 h, cooling the product, centrifuging, washing with ethyl acetate three times, and drying to obtain the composite modifier;
[0043] (3) 80 g of PEO matrix was added to 400 g of acetonitrile and mixed evenly, and then 35 g of lithium hexafluorophosphate, 20 g of composite modifier, and 8 g of ethoxy (pentafluoro) cyclotriphosphazene were added, and the mixture was stirred and dispersed at 80° C. for 2 h to obtain a casting slurry, and the slurry was cast into a film. After the solvent evaporated, the composite solid electrolyte was obtained.
[0044] Example 2
[0045] A method for preparing a composite solid electrolyte comprises the following steps:
[0046] (1) Dispersing 10 g of mesoporous silica and 2 g of KH570 in 100 mL of anhydrous ethanol, adding 1.0 mL of triethanolamine, and reacting at 70° C. for 4 h, filtering the product, washing with alcohol, and drying to obtain pretreated silica;
[0047] (2) dispersing 10 g of pretreated silica into 100 mL of ethyl acetate, ultrasonically treating for 20 min, then adding 15 mL of hexafluorobutyl acrylate and 15 mL of polyethylene glycol methyl ether acrylate, continuously introducing nitrogen, adding 0.4 g of azobisisobutyronitrile, stirring and reacting at 70 ° C for 6 h, cooling the product, centrifuging, washing with ethyl acetate three times, and drying to obtain the composite modifier;
[0048] (3) 70 g of PEO matrix was added to 350 g of acetonitrile and mixed evenly, and then 30 g of lithium hexafluorophosphate, 16 g of composite modifier, and 6 g of ethoxy (pentafluoro) cyclotriphosphazene were added, and the mixture was stirred and dispersed at 60° C. for 6 h to obtain a casting slurry, and the slurry was cast into a film. After the solvent evaporated, the composite solid electrolyte was obtained.
[0049] Example 3
[0050] A method for preparing a composite solid electrolyte comprises the following steps:
[0051] (1) Dispersing 10 g of mesoporous silica and 1 g of KH570 in 100 mL of anhydrous ethanol, adding 0.5 mL of triethanolamine, and reacting at 60° C. for 5 h, filtering the product, washing with alcohol, and drying it to obtain pretreated silica;
[0052] (2) dispersing 10 g of pretreated silica into 100 mL of ethyl acetate, ultrasonically treating for 30 min, then adding 10 mL of hexafluorobutyl acrylate and 20 mL of polyethylene glycol methyl ether acrylate, continuously introducing nitrogen, adding 0.3 g of azobisisobutyronitrile, stirring and reacting at 65 ° C for 10 h, cooling the product, centrifuging, washing with ethyl acetate three times, and drying to obtain the composite modifier;
[0053] (3) 60 g of PEO matrix was added to 300 g of acetonitrile and mixed evenly, and then 25 g of lithium hexafluorophosphate, 14 g of composite modifier, and 5 g of ethoxy (pentafluoro) cyclotriphosphazene were added, and the mixture was stirred and dispersed at 40° C. for 10 h to obtain a casting slurry, and the slurry was cast into a film. After the solvent evaporated, the composite solid electrolyte was obtained.
[0054] Example 4
[0055] A method for preparing a composite solid electrolyte comprises the following steps:
[0056] (1) Dispersing 10 g of mesoporous silica and 0.3 g of KH570 in 100 mL of anhydrous ethanol, adding 0.15 mL of triethanolamine, and reacting at 50° C. for 6 h. Filtering, washing with alcohol, and drying the product to obtain pretreated silica;
[0057] (2) dispersing 10 g of pretreated silica into 100 mL of ethyl acetate, ultrasonically treating for 30 min, then adding 10 mL of hexafluorobutyl acrylate and 20 mL of polyethylene glycol methyl ether acrylate, continuously introducing nitrogen, adding 0.05 g of azobisisobutyronitrile, stirring at 60 ° C for 12 h, cooling the product, centrifuging, washing with ethyl acetate three times, and drying to obtain the composite modifier;
[0058] (3) 60 g of PEO matrix was added to 300 g of acetonitrile and mixed evenly, and then 15 g of lithium hexafluorophosphate, 10 g of composite modifier, and 3 g of ethoxy (pentafluoro) cyclotriphosphazene were added, and the mixture was stirred and dispersed at 20° C. for 12 h to obtain a casting slurry, and the slurry was cast into a film. After the solvent evaporated, the composite solid electrolyte was obtained.
[0059] Comparative Example 1
[0060] A method for preparing a solid electrolyte comprises the following steps:
[0061] (1) Dispersing 10 g of mesoporous silica and 3 g of KH570 in 100 mL of anhydrous ethanol, adding 1.5 mL of triethanolamine, and reacting at 80° C. for 2 h, filtering the product, washing with alcohol, and drying to obtain pretreated silica;
[0062] (2) dispersing 10 g of pretreated silica into 100 mL of ethyl acetate, ultrasonically treating for 30 min, then adding 15 mL of hexafluorobutyl acrylate, continuously introducing nitrogen, adding 0.5 g of azobisisobutyronitrile, stirring and reacting at 75 ° C for 4 h, cooling the product, centrifuging, washing with ethyl acetate for 3 times, and drying to obtain the composite modifier;
[0063] (3) 80 g of PEO matrix was added to 400 g of acetonitrile and mixed evenly, and then 35 g of lithium hexafluorophosphate, 20 g of composite modifier, and 8 g of ethoxy (pentafluoro) cyclotriphosphazene were added, and the mixture was stirred and dispersed at 80° C. for 2 h to obtain a casting slurry, and the slurry was cast into a film. After the solvent evaporated, the solid electrolyte was obtained.
[0064] Comparative Example 2
[0065] A method for preparing a solid electrolyte comprises the following steps:
[0066] (1) Dispersing 10 g of mesoporous silica and 3 g of KH570 in 100 mL of anhydrous ethanol, adding 1.5 mL of triethanolamine, and reacting at 80° C. for 2 h, filtering the product, washing with alcohol, and drying to obtain pretreated silica;
[0067] (2) dispersing 10 g of pretreated silica into 100 mL of ethyl acetate, ultrasonically treating for 30 min, then adding 15 mL of polyethylene glycol methyl ether acrylate, continuously introducing nitrogen, adding 0.5 g of azobisisobutyronitrile, stirring and reacting at 75 ° C for 4 h, cooling the product, centrifuging, washing with ethyl acetate three times, and drying to obtain the composite modifier;
[0068] (3) 80 g of PEO matrix was added to 400 g of acetonitrile and mixed evenly, and then 35 g of lithium hexafluorophosphate, 20 g of composite modifier, and 8 g of ethoxy (pentafluoro) cyclotriphosphazene were added, and the mixture was stirred and dispersed at 80° C. for 2 h to obtain a casting slurry, and the slurry was cast into a film. After the solvent evaporated, the solid electrolyte was obtained.
[0069] Comparative Example 3
[0070] A method for preparing a solid electrolyte comprises the following steps:
[0071] (1) Dispersing 10 g of mesoporous silica and 3 g of KH570 in 100 mL of anhydrous ethanol, adding 1.5 mL of triethanolamine, and reacting at 80° C. for 2 h, filtering the product, washing with alcohol, and drying to obtain pretreated silica;
[0072] (2) 80 g of PEO matrix was added to 400 g of acetonitrile and mixed evenly, and then 35 g of lithium hexafluorophosphate, 20 g of pretreated silica, and 8 g of ethoxy (pentafluoro) cyclotriphosphazene were added, and the mixture was stirred and dispersed at 80° C. for 2 h to obtain a casting slurry, and the slurry was cast into a film. After the solvent evaporated, the solid electrolyte was obtained.
[0073] The solid electrolyte membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were made into 20 mm × 75 mm strip specimens. The initial distance between the clamps was set to 50 ± 5 mm. The two ends of the specimen were placed in the upper and lower ends of the clamps in turn, and the clamps were clamped. During the process, the specimen and the clamps were ensured to be in the same vertical direction and to be evenly stressed without obvious tensile deformation. After the preparation was completed, the tensile strength test was carried out at a rate of 150 ± 10 mm / min.
[0074] The solid electrolytes prepared in the embodiments and comparative examples were made into films with a thickness of 60±3 μm and tested using a CMT4000 electronic testing machine from MTS. The maximum load when a needle with a spherical front end (radius of curvature R: 0.5 mm) and a diameter of 1 mm was inserted into the film at a speed of 2 mm / s was measured to test its penetration resistance.
[0075] The solid electrolytes prepared in the embodiments and comparative examples were assembled into soft-pack batteries with graphite negative electrode sheets and ternary positive electrode sheets under the same conditions. At a temperature of 25°C±2°C, in the first step, they were charged at 0.1C or a specified current to the termination voltage, with a cutoff current of 0.01C, and allowed to stand for 30 minutes; in the second step, they were discharged at 0.1C to the final discharge voltage (2.75V), the discharge capacity was recorded, and the batteries were allowed to stand for 30 minutes; the first and second steps were repeated to test the cycle performance of the batteries for 300 cycles.
[0076] After the composite solid electrolyte membrane is pressed into a sheet, it is placed in a mold sleeve at 60° C. and pressurized. An AC impedance spectrum test is performed using an impedance analyzer, and the ionic conductivity of the electrolyte material is calculated based on the impedance value.
[0077] The solid electrolyte membrane was cut into discs with a diameter of 100 mm, placed in an oven at 150° C. for 1 h, taken out and the diameter of the discs was measured again, and the thermal shrinkage of the solid electrolyte membrane was calculated.
[0078] The specific test results are shown in Table 1.
[0079] Table 1 Solid electrolyte performance test results
[0080]
[0081] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A composite solid electrolyte, characterized in that: The invention is prepared from the following components by weight: 60-80 parts of PEO matrix, 15-35 parts of lithium salt, 10-20 parts of composite modifier and 3-8 parts of ethoxy (pentafluoro) cyclotriphosphazene.
2. The composite solid electrolyte according to claim 1, characterized in that The preparation method of the composite modifier comprises the following steps: (1) Dispersing mesoporous silica and KH570 in anhydrous ethanol, adding triethanolamine, refluxing reaction, filtering, washing with alcohol, and drying the product to obtain pretreated silica; (2) dispersing the pretreated silica in ethyl acetate, ultrasonically treating, then adding hexafluorobutyl acrylate and polyethylene glycol methyl ether acrylate, continuously introducing nitrogen, adding azobisisobutyronitrile, stirring to react, cooling, centrifuging, washing, and drying the product to obtain the composite modifier.
3. The composite solid electrolyte according to claim 2, characterized in that: In step (1), the usage ratio of mesoporous silica, KH570, anhydrous ethanol and triethanolamine is 10 g: 0.3-3 g: 50-100 mL: 0.15-1.5 mL.
4. The composite solid electrolyte according to claim 2, characterized in that: In step (1), the reflux reaction conditions are 50-80° C. for 2-6 hours.
5. The composite solid electrolyte according to claim 2, characterized in that: In step (2), the usage ratio of pretreated silica, ethyl acetate, hexafluorobutyl acrylate, polyethylene glycol methyl ether acrylate, and azobisisobutyronitrile is 10 g: 100-150 mL: 10-15 mL: 15-20 mL: 0.05-0.5 g.
6. The composite solid electrolyte according to claim 2, characterized in that: In step (2), the ultrasonic treatment is performed for 10 to 30 minutes; the stirring reaction conditions are 60 to 75° C. and the stirring reaction is performed for 4 to 12 hours; and the product is washed with ethyl acetate for 3 to 5 times.
7. The composite solid electrolyte according to claim 1, characterized in that: The lithium salt is one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium chloride.
8. A method for preparing the composite solid electrolyte according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: adding a PEO matrix into a solvent, mixing evenly, then adding a lithium salt, a composite modifier, and ethoxy (pentafluoro) cyclotriphosphazene, stirring and dispersing evenly to obtain a casting slurry, casting the slurry into a film, and obtaining the composite solid electrolyte after the solvent evaporates.
9. The preparation method according to claim 8, characterized in that: The solvent is one or more of acetonitrile, acetone, DMF and NMP; the mass ratio of the PEO matrix to the solvent is 1:5-10.
10. The preparation method according to claim 8, characterized in that: The stirring and dispersing conditions are 20 to 80° C. for 1 to 12 hours.
Citation Information
Patent Citations
PEO-based solid electrolyte and preparation method thereof
CN118136940A
Modified nano silicon dioxide and preparation method and application thereof
CN111416146A
Novel fluorine-containing composite lithium ion solid electrolyte and preparation method thereof
CN114566699A
Organic-inorganic co-modified PEO solid electrolyte and preparation method thereof
CN117525574A
Preparation and application of flame-retardant solid electrolyte
CN117790913A
Cited By
3D printing composite solid electrolyte and solid-state battery
CN121215873A